Materialni pogoji in diskurzi dediščine popularne glasbe v Sloveniji - Zevnik, Luka (Družboslovne razprave, 2013)
The article draws research into popular music together with the rapidly developing field of heritage studies. The central question is how to think of (Slovenian) popular music in heritage terms from theoretical, methodological and empirical perspectives. The article first develops a theoretical and methodological framework to analyse popular music heritage and then applies it to the case of Slovenia. While several official institutions collect certain material aspects of popular music heritage, the discursive analysis and the in-depth interviews with music experts suggest it is impossible to speak of an official discourse of popular music heritage. The existing discourses and practices of popular music heritage are mostly limited to NGO organisations and DIY popular music collectors.
Keywords: Popular music; Volkstümliche Musik; Zabavna glasba; Kulturna dediščina; cultural heritage; Cultural property; History; Zgodovina; Cultural policy; Kulturna politika; Slovenia; Slovenija; popularna glasba